Monitoring dan Pencegahan Serangan Judi Online (Slot Gacor) pada Website - Alim, Endi Sjaiful; Nuroji, Nuroji; Rizkiawan, M. Asep; Anhari, Tirta; Sobari, Bahar (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
A website is a complex tool for presenting information. The security of a website is very important to support the reputation of the website. The rise of online gambling has now penetrated the website, the most dangerous is when the website has been infiltrated with an online gambling page. The purpose of the research is to prevent and monitor the website against online gambling hacker attacks. This research uses a descriptive method approach, namely by monitoring and observing the website, we try to provide an in-depth explanation of monitoring and preventing online gambling attacks (Slot Gacor) by utilizing Cloudflare services. Cloudflare is implemented as a security system on the website. In this research, the website that became a case study was the bpti.uhamka.ac.id website with the research location in the UHAMKA data center room. Data collection techniques and data analysis are carried out by direct observation through the cloudflare website. The data analyzed in the form of graphs and money url paths have been blocked. Research results Within 8 days there were 126 url paths that could be blocked by cloudflare and all of them contained online gambling with most of them being gacor slots. Cloudflare has successfully blocked hackers by filtering path URLs from the originating website.